Pengaruh Konsumsi Ikan terhadap Peningkatan Tinggi Badan Balita Stunting (Studi Intervensi): The Effect of Fish Consumption on Increasing the Height of Stunted Toddlers (Intervention Study) - Witradharma, Tetes Wahyu; Mahyuddin, Meriwati (Universitas Airlangga, 2026)
Background: The proportion of stunted toddlers is 19.8%, and 12.9% in Bengkulu Province and Bengkulu City, respectively. Indicating that the prevalence of stunting among toddlers remains high in Indonesia. Stunted toddlers experience impaired growth, dysfunctional immune system and are more susceptible to diseases. Maternal lack of knowledge on dietary needs reduces their role in meeting toddler nutritional requirements, exclusive breastfeeding and fish-based complementary foods. Objectives: To determine the effects of fish consumption on height of stunted toddlers. Methods: The study used a quasi-experimental non-equivalent (pretest and post-test) control group design, conducted on intervention and control groups for 2 months (8 weeks). The intervention group received the Toddler Feeding Program, while the control group received local Community Health Center Program. The sample consisted of all stunted toddlers aged 6-18 months in North Bengkulu Regency Health Office's work area. Data analysis was performed using Stata 16. For univariate analyses, variables including education, occupation, gender, age of mother and toddler, and toddler fish consumption patterns were considered. Bivariate analyses were conducted using independent t-test to assess differences in body length. Results: Consumption of freshwater, saltwater, and brackish water fish in the intervention group was higher than those in the control group (28.13±48.43 and 19.17±16.89; 23.54±26.92 and 14.79±12.47; 1.88±5.07 and 0.21±0.79). Maternal behaviors towards toddlers, including knowledge (7.83±4.62), attitudes (8.71±5.12), and actions (7.63±4.62) in the intervention group was higher than those in the control group (4.96±4.70; 5.46±5.13; 4.83±4.58). The height of stunted toddlers in the intervention group (0.71±0.59) was higher than the control group (0.46±0.48) with a Pearson coefficient of 0.002. Conclusions: This study shows that fish consumption is associated with improved growth of stunted toddlers.